The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2215/cjn.02180314
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Growth after Kidney Transplantation among Children with ESRD

Abstract: Background and objectives Poor linear growth is a frequent complication of CKD. This study evaluated the effect of kidney transplantation on age-related growth of linear body segments in pediatric renal transplant recipients who were enrolled from May 1998 until August 2013 in the CKD Growth and Development observational cohort study.Design, setting, participants, & measurements Linear growth (height, sitting height, arm and leg lengths) was prospectively investigated during 1639 annual visits in a cohort of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 38 publications
2
60
0
Order By: Relevance
“…Growth is also significantly impacted in pediatric patients with ESRD, and therefore, catch‐up growth following KT is an important consideration for pediatric KT recipients. Those with poor graft function (eGFR <50 mL/min/1.73 m 2 ) may have limited catch‐up growth following KT . However, in both pre‐emptive and post‐dialysis groups, the majority of the patients were able to maintain a minimum eGFR ≥60 mL/min/1.73 m 2 , suggesting that both pre‐emptive and post‐dialysis KT are effective in maintaining renal function in the first year following KT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth is also significantly impacted in pediatric patients with ESRD, and therefore, catch‐up growth following KT is an important consideration for pediatric KT recipients. Those with poor graft function (eGFR <50 mL/min/1.73 m 2 ) may have limited catch‐up growth following KT . However, in both pre‐emptive and post‐dialysis groups, the majority of the patients were able to maintain a minimum eGFR ≥60 mL/min/1.73 m 2 , suggesting that both pre‐emptive and post‐dialysis KT are effective in maintaining renal function in the first year following KT.…”
Section: Discussionmentioning
confidence: 99%
“…In both adult and pediatric population, it has been suggested that 1 year post‐transplant eGFR is prognostic of favorable graft survival . Moreover, graft function following pediatric KT has shown to be an important factor for growth in children . Thus, the assessment of renal function following KT in pre‐emptive and post‐dialysis pediatric KT recipients allows understanding of whether there is an added benefit to pre‐emptive KT that may contribute to other outcomes, while also elucidating the potential difference in the natural history of graft function changes in the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…In patients on renal replacement therapy, persistent Fanconi syndrome may impair bone health, and native kidney nephrectomy might be considered. Minimal glucocorticoid exposure should be considered to permit attainment of a normal adult height . Preservation of transplant function and optimizing metabolic control can further improve growth .…”
Section: Cystinosis Metabolic Bone Diseasementioning
confidence: 99%
“…64,65 Preservation of transplant function and optimizing metabolic control can further improve growth. 64 GH may be started in case of persistent short stature (>12 months after transplantation). In addition, early and diligent physical and rehabilitation therapy, including muscle strengthening and targeted exercise, can prevent and/or improve skeletal deformities, and possibly eliminate the need for extensive orthopedic surgeries.…”
Section: Management Of Cmbdmentioning
confidence: 99%
“…Corticosteroid exposure has been shown to be negatively associated with post–solid organ transplant linear growth 82 85 . Chronic corticosteroid use is not limited to solid organ transplant recipients.…”
Section: Special Population Considerationsmentioning
confidence: 99%